PENJATUHAN SANKSI PIDANA PORNOGRAFI MELALUI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK: Penalty of Pornography Through The Electronic Information and Transaction Law - Aurellia Amanda Sherly; Eriyantouw Wahid (Reformasi Hukum Trisakti, 2025)
The imposition of criminal sanctions against the perpetrator of the pornographic model of the defendant by the name of Yuli Hertina live streaming herself naked and the defendant received benefits from these actions. The judge decided with Article 27 paragraph (1) of Law Number 11 of 2008 concerning Electronic Information and Transactions. As with the study of decision number 459/Pid.Sus/2023/PN JKT.SEL, the main problem is whether the imposition of criminal sanctions on the perpetrators of criminal acts of pornography is included in the category in Article 27 paragraph (1) of the Electronic Information and Transactions Law. This research method uses normative juridical, using primary and secondary data, qualitative approach data collection techniques, descriptive data analysis. The results and conclusions of the discussion indicate that the perpetrator's actions of committing pornography by displaying nudity and masturbation via live streaming fall under the category of pornography. Therefore, the judge should have applied Article 27(1) of the ITE Law in conjunction with Article 8 of the Pornography Law. The imposition of criminal sanctions by the judge against the perpetrator of pornography is inappropriate because it does not fall under the category of Article 27(1) of the ITE Law.